Приведите одночлен к стандартному виду:51) 2ab×(-3)(ab)^252) (-2)×a^2×(-3)(b)^353) (ab^2)^2×(-4a)^254) b×(-3a)^3×a^255) ab×(-2)×(4a)^356) 3a×(-2b)^2×3b57) 2ab×(-4)×(3a)^258) 3a×(-2)×(2b)^359) ab×4a×(-3b)^360) (2ab)^2×(-3)×b

Приведите одночлен к стандартному виду: 51) 2ab×(-3)(ab)^2 52) (-2)×a^2×(-3)(b)^3 53) (ab^2)^2×(-4a)^2 54) b×(-3a)^3×a^2 55) ab×(-2)×(4a)^3 56) 3a×(-2b)^2×3b 57) 2ab×(-4)×(3a)^2 58) 3a×(-2)×(2b)^3 59) ab×4a×(-3b)^3 60) (2ab)^2×(-3)×b
Гость
Ответ(ы) на вопрос:
Гость
2ab·(-3)(ab)²= -6a³b³ -2a²·(-3)b³ = 6a²b³ (ab²)²·(-4a)²= a²b⁴·16·a²=16a⁴b⁴ b·(-3a)³·a² = -27a⁵b ab·(-2)·(4a)³ =  -128a⁴b  3a·(-2b)²·3b=3a·4b²·3b= 36ab³  2ab·(-4)·(3a)²= 2ab·(-4)·9a²=  -72a³b  3a·(-2)·(2b)³= -6a·8b³= -48ab³  ab·4a·(-3b)³= 4a²b·(-27)·b³= -108 a²b⁴  (2ab)²·(-3)·b= 4a²b² · (-3)b= -12a²b³  
Не нашли ответ?
Ответить на вопрос
Похожие вопросы